Indebtedness and Subjective Financial Wellbeing of Households in Indonesia - Dwini Handayani; Ummu Salamah; Restananda Nabilla Yusacc (Economics and Finance in Indonesia, 2016)
Indebtedness is an element to foresee household financial wellbeing. This vulnerability could be determined objectively and subjectively. Objective financial vulnerability is the objective ability to make ends meet that is analyzed using household income and characteristics. Measurement in subjective welbeing is determined by household perceptions in their ability to make ends meet. Household behavior with different perceptions will behave differently. Indebtedness is analyzed using the Indonesian Family Life Survey (IFLS) 5 with the Ordinary Least Square method. The inferential shows that both objective and subjective financial wellbeing influence household indebtedness. AbstrakKedalaman hutang merupakan elemen untuk mengetahui kesejahteraan finansial rumah tangga. Kerentanan ini dapat dilihat secara objektif maupun subjektif. Kerentanan finansial objektif adalah kemampuan objektif dalam memenuhi kebutuhan sehari-hari menggunakan pendapatan rumah tangga dan karakteristiknya. Ukuran dari kesejahteraan subjektif ditentukan oleh persepsi rumah tangga dalam kemampuannya untuk memenuhi kebutuhan sehari-hari. Rumah tangga dengan persepsi berbeda akan memiliki perilaku yang berbeda pula. Kedalaman rumah tangga dianalisis menggunakan Indonesian Family Life Survey (IFLS) 5 dengan metode Ordinary Least Square. Hasil analisis menunjukkan bahwa, baik kesejahteraan rumah tangga objektif maupun kesejahteraan rumah tangga subjektif memengaruhi kedalaman hutang rumah tangga.Kata kunci: Perilaku Rumah Tangga; Ekonomi Keluarga; Kedalaman Rumah Tangga; Kesejahteraan SubjektifJEL classifications: D10; D31